DIVERSITY AND ABUNDANCE OF BUTTERFLY TYPES AROUND IN CIRAHAB SUMBER AREA CURUGGOONG VILLAGE PADARINCANG DISTRICT SERANG REGENCY - Hermawan, Hermawan (Transpublika Publisher, 2024)
This research aims to determine the diversity and abundance of butterfly species (Lepidoptera) in the Cirahab Sumber area. The method used in this research is quantitative descriptive methods. In this study, samples were taken from the Cirahab Sumber area, several families were obtained, including the Nymphalidae, Pieridae, Papilioidae, Lycaenidae, Hesperiidae families. The most frequently obtained family was Nymphalidae, with 10 types of butterflies obtained and the least was from the family Lycaenidae, Hesperiidae with only 2 species. The calculation results of the H' or diversity index value in this study obtained a value of 2.940142703, this value shows the